Livelihood strategies and land management practices in the highlands of Tigray - Pender, J.L.; Gebremedhin, Berhanu; Haile, M. (International Food Policy Research Institute, 2002)
This paper investigates the livelihood strategies and land management practices used in the highlands of Tigray region, the factor influencing them, and their implications for crop production and income, livestock income and investment, other sources of income, and farmers; perceptions of land degradation. The findings of the study shows that profitable opportunities exist to increase agricultural production, household incomes and achieve more sustainable land management in the highlands of Tigray. The paper ends with comment from Frank Place.